Ecotoxicological parameters of the application of biopesticides, development and adaptation of biological systems of apple protection against pests and diseases to the soil-climatic and phytosanitary conditions of the agrocenose - Borzykh, O.; Bublyk, L.; Hunchak, M.; Gavrylyuk, L.; Shevchuk, O.; Vlasova , O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. Ecotoxicological and economic substantiation of the biological system of apple protection against pests and diseases, its optimization and adaptation to the weather and climatic conditions and the phytosanitary state of apple agrocenosis in the Precarpathian province of the Carpathian mountain zone of Ukraine in order to reduce crop losses and improving its quality.Methods. Phytosanitary monitoring was performed visually and using pheromone traps. The degree of hazard of pesticides was assessed by an integrated 7-point scale, the risk — by agroecotoxicological index (AETI).Results. Based on the monitoring of the phytosanitary state of the apple agrocenosis in 2015—2017, scientific and methodological parameters of ecologically safe and cost-effective protection systems for apple trees adapted to the soil and climatic conditions of the Precarpathian province of the Carpathian mountain zone of Ukraine were developed: biological and biological-chemical. They are based on 7 treatments with biological or chemical and biological preparations, carried out in the phenophases of culture critical for the development of harmful organisms. The efficiency of the biological system against harmful organisms was in the range of 65.7—72.8%, the biological-chemical system — 66.4—96.5%. It is shown that replacing a number of chemical treatments with biological ones allows to minimize the negative impact of pesticides on the apple agrocenosis.Conclusions. A model of ecologically safe protection of an apple orchard against a complex of harmful organisms has been developed. It is shown that the modern assortment of biological protection means makes it possible to develop a system that provides effective protection of the apple orchard against a complex of diseases and pests. Calculations showed that the system of biological and chemical protection was more effective in terms of profitability during the years of research (71.4—127.23%). The profit obtained from the use of this system was from 49 898.9 to 107 586.4 UAH/ha.